TRANSLATION METHOD USED IN TRANSLATING SHORT STORY “THE GIFT OF THE MAGI” BY HARUM WIBOWO - Laia, Marnidewi; Wau, Senadaman; Zagoto, Impiani (Universitas Nias Raya, 2021)
The aims of this research were to find out kinds of translation method and to find out the most dominants kinds of translation method used by Harum Wibowo in translating short story “The Gift of the Magi”. This research was conducted by using Qualitative research to analyze the translation methods used by Harum Wibowo in translating short story “The Gift of the Magi”. The data were analyzed by reading both English and Indonesian version of the short story classifying each sentence according to each translation methods and explaining why the utterances are included into each translation methods. There were 125 utterances in short story “The Gift of the Magi”. The result shows that there were 6 kinds of 8 translation methods found in translation short story “The Gift of the Magi”. the translation methods used by the translator in translating short story, word for word translation (2 utterances), literal translation (34 utterances), faithful translation (33 utterances), free translation (53 utterances), idiomatic translation (1 utterance), and communicative translation (2 utterances). Free translation method is more frequently used because the translator tried to make the target reader understand as far as possible. These results are expected will give a new insight for teacher and students about translation method and more be carefully in using translation method in order to make a better translation.